Ketogenic diets in clinical psychology: examining the evidence and implications for practice - Laurent, Nicole; Bellamy, Erin L.; Hristova, Donika; Houston, Ally (Frontiers in Psychology, 2024)
Introduction: The application of ketogenic dietary interventions to mental health treatments is increasingly acknowledged within medical and psychiatric fields, yet its exploration in clinical psychology remains limited. This article discusses the potential implications of ketogenic diets, traditionally utilized for neurological disorders, within broader mental health practices.Methods: This article presents a perspective based on existing ketogenic diet research on historical use, biological mechanisms, and therapeutic benefits. It examines the potential application of these diets in mental health treatment and their relevance to clinical psychology research and practice.Results: The review informs psychologists of the therapeutic benefits of ketogenic diets and introduces to the psychology literature the underlying biological mechanisms involved, such as modulation of neurotransmitters, reduction of inflammation, and stabilization of brain energy metabolism, demonstrating their potential relevance to biopsychosocial practice in clinical psychology.Conclusion: By considering metabolic therapies, clinical psychologists can broaden their scope of biopsychosocial clinical psychology practice. This integration provides a care model that incorporates knowledge of the ketogenic diet as a treatment option in psychiatric care. The article emphasizes the need for further research and training for clinical psychologists to support the effective implementation of this metabolic psychiatry intervention.